Developing Pesantren Educator Resources through Optimizing the Learning Organization - Ma`arif, Muhammad Anas; Mumtahana, Lusia; Sunarno, Sunarno; Mansyuri, Arif; Nasith, Ali (Nazhruna: Jurnal Pendidikan Islam, 2023)
This article aims to describe the application of the Learning Organization in developing the competence of teacher educator resources in pesantren. This research has been conducted at Amanatul Ummah Islamic Boarding School (Madrasah Bertaraf Internasional). The research that has been used is qualitative with a case study approach. The data collection techniques use interviews with informants, namely, the head of the MBI coordinator, teachers, and some students. Observation involves past participant observation, and documentation includes reviewing data related to professional development carried out by teachers. The findings of this study are as follows: strict recruitment of education personnel who are under the pesantren's national insight and affiliated with Aswaja NU, strengthening the pesantren organizational culture through leadership training via administrative activities, and teachers conducting scientific integration, combining the Egyptian Al Azhar curriculum with the national curriculum. Teachers' professional development must be supported by pesantren, which provides more compensation and discipline in carrying out teachers' duties.